Optimum-cost-based renewable energy chart considering micro-hydro, solar-PV, and hybrid systems using HOMER suitable for eastern Himalayan regions of India - Adikanda Parida; Bikuk Lomdak (Institute of Advanced Engineering and Science, 2023)
The climatic change issues can only be addressed by adding more and more renewable energy into the energy chart for any region. However, the criteria for the composition of the chart shall be based on availability, cost-effectiveness, complementary nature, and optimally fit with the load curve. Based on the geographical diversity and availability of renewable energy in India, the energy chart is different for different regions. In this paper, an attempt has been made to prepare a renewable energy chart based on the equality constraint optimization technique for economical load sharing between the locally available renewable energy sources. The HOMER-based software platform has been utilized for cost analysis purposes. Based on locally available renewable energy sources, micro-hydro, and solar-PV are considered for analysis. In this paper, the electrical load of an educational institution situated in the eastern Himalayan region is considered for the case study. The data received from the case study has been utilized for the preparation of an appropriate and economically viable renewable energy chart for the mentioned region. Even though the analysis model applies to a particular region, it can be suitably modified for other regions also.